Cell Inertia: Predicting Cell Distributions in Lung Vasculature to Optimize Re-endothelialization - Chan, Jason K.D.; Chadwick, Eric A.; Taniguchi, Daisuke; Ahmadipour, Mohammadali; Suzuki, Takaya; Romero, David; Amon, Cristina; Waddell, Thomas K.; Karoubi, Golnaz; Bazylak, Aimy (Frontiers in Bioengineering and Biotechnology, 2022)
We created a transient computational fluid dynamics model featuring a particle deposition probability function that incorporates inertia to quantify the transport and deposition of cells in mouse lung vasculature for the re-endothelialization of the acellular organ. Our novel inertial algorithm demonstrated a 73% reduction in cell seeding efficiency error compared to two established particle deposition algorithms when validated with experiments based on common clinical practices. We enhanced the uniformity of cell distributions in the lung vasculature by increasing the injection flow rate from 3.81 ml/min to 9.40 ml/min. As a result, the cell seeding efficiency increased in both the numerical and experimental results by 42 and 66%, respectively.